Вплив живопису слобожанських художників на пейзажну лірику Анатолія Перерви - Писаревська, Oксана Вікторівна; Pisarevskaya, Oksana (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті досліджено вплив художників-пейзажистів на творчість відомого українського поета Анатолія Перерви. Праця допомагає краще зрозуміти творчу лабораторію письменника, визначити, що є джерелом творчого натхнення для митця, глибше проникнути в ідейно-естетичний зміст його творів. The article investigates the influence of landscape painters on the work of the famous Ukrainian poet Anatoly Pererva. The study helps to better understand the «creative laboratory» of the poet, to determine what is the source of inspiration for the artist, penetrate deeper into the ideological and aesthetic content of his works. As a result of the study there were considered the basic stages of development of pastoral poetry A. Pererva; there was determined the circle of artists (S. Vasilkovsky, N. Verbuk, Dziubenko V., Bondar), paintings that served as a source for artistic expression A. Pererva; there was shown the presence of isomorphism in the ways of expressing the ideological and aesthetic content between painting S. Vasilkovsky and landscape poetry A. Pererva; isomorphic relationship is reflected in the nature of the objective world, the use of color, description of heaven, humanization of the landscape; there was considered the influence of paintings by other artists in the landscape poetry A. Pererva.
The Influence of Artists Slobozhansky Painting on the Anatoly Pererva’s Pastoral Poetry
Keywords: живопис; ідейно-естетичний задум; ізоморфізм; пейзажна лірика; пейзажний живопис; painting; ideological and aesthetic purpose; isomorphism; landscape poetry; landscape painting